Hybrid renewable energy systems - Sahoo, Umakanta (Wiley-Scrivener, 2021)
"The energy scene in the world is a complex picture of a variety of energy sources being used to meet the world's growing energy needs. There is, however, a gap in the demand and supply. It is recognized that decentralized power generation based on the various renewable energy technologies can, to some extent, help in meeting the growing energy needs. The renewable energy landscape has witnessed tremendous changes in the policy framework with accelerated and ambitious plans to increase the contribution of renewable energy such as solar, wind, bio-power, and others. Hybrid renewable energy systems are important for continuous operation and supplements each form of energy seasonally, offering several benefits over a stand-alone system. It can enhance capacity and lead to greater security of continuous electricity supply, among other applications. This book provides a platform for researchers, academics, industry professionals, consultants and designers to discover state-of-the-art developments and challenges in the field of hybrid renewable energy. Written by a team of experts and edited by one of the top researchers in hybrid renewable systems, this volume is a must-have for any engineer, scientist, or student working in this field, providing a valuable reference and guide in a quickly emerging field"--